2021
DOI: 10.3389/fonc.2021.768009
|View full text |Cite
|
Sign up to set email alerts
|

Biliary Tract Cancers: Treatment Updates and Future Directions in the Era of Precision Medicine and Immuno-Oncology

Abstract: The effective management of biliary tract cancers (BTCs) has been hampered by limited options for systemic therapy. In recent years, the focus on precision medicine has made technologies such as next-generation sequencing (NGS) accessible to clinicians to identify targetable mutations in BTCs in tumor tissue (primarily) as well as blood, and to treat them with targeted therapies when possible. It has also expanded our understanding of functional pathways associated with genetic alterations and opened doors for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 171 publications
(186 reference statements)
0
20
0
1
Order By: Relevance
“…Recently, the principle of targeted therapy has gained traction for cholangiocarcinoma. Based on specific targetable mutations (e.g., IDH1, FGFR2, VEGF, and NTRK) several (second-line) therapies have shown promising prolonged OS and have been approved, mainly for iCC [44,45]. Together with immunotherapy [44], survival rates are expected to further improve in the future.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, the principle of targeted therapy has gained traction for cholangiocarcinoma. Based on specific targetable mutations (e.g., IDH1, FGFR2, VEGF, and NTRK) several (second-line) therapies have shown promising prolonged OS and have been approved, mainly for iCC [44,45]. Together with immunotherapy [44], survival rates are expected to further improve in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Based on specific targetable mutations (e.g., IDH1, FGFR2, VEGF, and NTRK) several (second-line) therapies have shown promising prolonged OS and have been approved, mainly for iCC [44,45]. Together with immunotherapy [44], survival rates are expected to further improve in the future. Recently, the TOPAZ-1 phase III study showed that combining cisplatin/gemcitabine with the PD-L1 inhibitor durvalumab further improved overall response rate (ORR), progression free survival (PFS), and median [46].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…FGFR2 gene fusions, such as FGFR2 – BICCI , FGFR2 – AHCYL1 , FGFR2 – TACC3 , and FGFR2 – KIAA1598 , are closely associated with tumor progression in iCCA [ 7 ]. The outcomes of clinical trials of small-molecule targeted therapies for these genetic alterations are presented in Table 3 [ 7 , 13 ]. Previous results indicated a maximum disease control rate (DCR) of 80% and progression-free survival (PFS) of approximately 6 months [ 14 , 20 , 21 ]; therefore, FGFR inhibitors are promising drugs for targeted therapies for CCA with FGFR2 fusions.…”
Section: Genetic Alterations In Cca and Clinical Trials Of Targeted T...mentioning
confidence: 99%
“…In recent years, the application of next-generation sequencing (NGS) technology has improved our knowledge of the molecular biology of cancer, as well as genetic alterations, and has expedited developments in targeted therapy for these alterations. Precision medicine involves the selection of suitable drugs, therapies, or preventive strategies based on an individual’s genotype or gene expression profile and clinical data, thereby achieving maximum therapeutic efficacy and minimal side effects [ 12 , 13 , 14 ]. This study describes the current state of precision medicine for CCA treatment.…”
Section: Introductionmentioning
confidence: 99%